A semantic type-driven account of verb-formation patterns in Panyjima - Caudal, P.; Dench, Alan; Roussarie, L. (2012)
In this paper we propose a semantic type-driven account of verb-formation patterns in Panyjima. By offering an explicit theory for the construal of semantically simplex event descriptions from morphologically complex verbal stems, we flesh out intuitions dating back to Clark and Clark (1979) about the role of derivational morphology in the interpretation of derived verbs, especially denominal verbs. This latter point is of particular relevance to a general theory of verb meaning (inclusive of, but not limited to, Aktionsart/lexical aspect), as most formal theories of lexical semantics have been primarily developed for languages with a rich verbal lexicon. By contrast, Australian languages often have a much smaller verbal lexicon and rely more heavily on productive processes of verbalization. The challenge we intend to meet is to provide a formal analysis that matches the productive morphology of the language under investigation. We offer an implementation couched within the Type Composition Logic (TCL) of Asher (2011), which demonstrates how TCL can successfully capture the contextual interpretation of productively derived Panyjima verbs. © 2012 The Australian Linguistic Society.